ZEOLITE CATALYSED SYNTHESIS OF 1-(4-AMINOPHENYL)-2-PHENYL-4- (4-SUBSTITUTED BENZYLIDENE)-5-IMIDAZOLONES. - R.M.KEDAR; S.A.DESHMUKH (International Journal of Pharma and Bio Sciences, 2016)
Imidazolones have gained immense significance due to their variety of applications as well as their diverse pharmacological action. In this work we have reported twelve newly synthesized imidazolones from oxazolones and phenylene diamine in presence of zeolite as a catalyst. The oxazolones in turn were obtained from benzoyl glycine and variedly substituted aromatic aldehydes in presence of acetic anhydride and sodium acetate .The characterization of these compounds was made by chemical properties, elemental analysis and spectral data like IR, 1H-NMR.The use of zeolite as a catalyst afforded us rapid synthesis of imidazolones and increase in their percent yield.